"I Miss My Liver." Nonmedical Sources in the History of Hepatocentrism. Issue 8 (6th August 2018) - Orlandi, Riccardo; Cianci, Nicole; Invernizzi, Pietro; Cesana, Giancarlo; Riva, Michele Augusto
Abstract : Hepatocentrism was a medical doctrine that considered the liver the center of the whole human being. It originated in ancient populations (Mesopotamic civilization) and persisted in Western countries until the seventeenth century. Hidden references to hepatocentrism may be found in artistic representations and literary works, from the myth of Prometheus in the Greco‐Roman world to the crucifixion iconography throughout the Middle Ages. In the mid‐1600s, fundamental discoveries irrefutably demonstrated the central role of the heart in human physiology, which laid the foundations for creating cardiocentrism, shifting the life's center from the liver to the heart. The advent of cardiocentrism immediately restricted the importance given to the liver, favoring the heart in the fine arts. Nevertheless, the liver maintained its importance in literature and popular belief as is evidenced by the widely acclaimed literary texts "Snow White" by the Brothers Grimm, "Moby Dick" by Herman Melville, and "Ode to the Liver" by Pablo Neruda. Our aim is to analyze the most significant artistic representations and literary works that contain references to hepatocentrism, evaluating the changing ideas and beliefs regarding the role and function of the liver throughout history. We want to underline the tight relationship between art and medicine; fine art and literature could be a valuable source for understanding the history of hepatology. ( Hepatology Communications 2018; 00:000‐000)